Analisis strategi pemasaran pada PT. Indofood Sukses Makmur Tbk - Wasil, Mohammad; Haikaya, Oktaviani Dewi; Nabila, Nina; Afrella, Galuh Rika; Alfindy, Moh (Implementasi Manajemen & Kewirausahaan, 2023)
Business strategy is the direction of actions or a series of decisions that assist entrepreneurs in achieving specific goals. It is a combination of all the decisions made from the actions taken by entrepreneurs to achieve business goals and to secure a competitive position in the market. The increasingly fierce business competition during the pandemic has prompted companies to have the right strategies to excel in competition with other companies or to sustain their business. This research focuses on companies operating in the food, seasoning, and beverage processing industry, with PT. Indofood Sukses Makmur Tbk as the sample. Founded as PT Panganjaya Intikusuma in 1990, the company has engaged in various business activities since the early 1980s. This writing aims to determine how PT. Indofood Sukses Makmur Tbk executes its business strategy using SWOT analysis in business development. The SWOT method is employed to describe and select the right strategies for the company's competitiveness. The result is that PT. Indofood Sukses Makmur Tbk consistently develops its business with a focus on market strategy to ensure the company's well-functioning and stability amid increasingly intense competition. Keywords: SWOT analysis, strategy analysis, strategy focus, PT Indofood Sukses Makmur Tbk.